2009
DOI: 10.1007/s11192-007-1984-5
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly communication in transition: The use of question marks in the titles of scientific articles in medicine, life sciences and physics 1966–2005

Abstract: The titles of scientific articles have a special significance. We examined nearly 20 million scientific articles and recorded the development of articles with a question mark at the end of their titles over the last 40 years. Our study was confined to the disciplines of physics, life sciences and medicine, where we found a significant increase from 50% to more than 200% in the number of articles with question-mark titles. We looked at the principle functions and structure of the titles of scientific papers, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
54
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 30 publications
6
54
0
2
Order By: Relevance
“…While Lewison and Hartley (2005) found that the nationality of authors did not affect title characteristics, Ball (2009) found national and regional differences in the use of question marks in article titles over a 40-year period he studied. These discrepancies might be described by the different disciplines studied, because researchers have found, analyzing the full text of articles, that disciplinary identity in medicine transcends national differences, while in ECN and linguistics the national writing tradition is more visible (Breivega et al, 2002;Dahl, 2004).…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…While Lewison and Hartley (2005) found that the nationality of authors did not affect title characteristics, Ball (2009) found national and regional differences in the use of question marks in article titles over a 40-year period he studied. These discrepancies might be described by the different disciplines studied, because researchers have found, analyzing the full text of articles, that disciplinary identity in medicine transcends national differences, while in ECN and linguistics the national writing tradition is more visible (Breivega et al, 2002;Dahl, 2004).…”
mentioning
confidence: 93%
“…In many scientific fields the principal type of scientific document is a research article ("paper"). Titles and the choice of words in them play two important roles: they inform the reader about the content of the paper, while at the same time attempting to trigger their attention (Bazerman, 1985(Bazerman, , 1988Ball, 2009). For the first role, the words are chosen to "convey credible information for a given population of producer-readers" (Callon et al, 1983, p. 199).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The former discuss titles in education, psychology and literary criticism (Dillon, 1982); in literature, linguistics and science (Haggan, 2004), in natural, medical and social sciences (Buxton and Meadow, 1977;Jaime Sisò, 2009;Pereira, Fadigas, Senna and Moret, 2011); in anthropology, biology, biochemistry, medicine, linguistics, psychology (Soler, 2007(Soler, & 2011; in medicine, life sciences and physics (Ball, 2009); in medicine and linguistics (Busch-Lauer, 2000); in biology, clinical medicine, oncology, chemistry, engineering and physics (Hartley, 2005(Hartley, & 2007Lewison and Hartley, 2005).…”
Section: Introductionmentioning
confidence: 99%